Formaldehyde, acetaldehyde and other aldehyde emissions from HCCI/SI gasoline engine equipped with prototype catalyst. (1st July 2016) - Hasan, Ahmad O.; Abu-jrai, Ahmad; Al-Muhtaseb, Ala'a H.; Tsolakis, Athanasios; Xu, Hongming
Highlights: Analysis of carbonyl compounds from exhaust gas of HCCI/SI engine was investigated. Acetaldehyde was the most abundant carbonyls in the exhaust for both HCCI/SI modes. Carbonyl species are heavily dependent on engine operation and combustion mode. The prototype catalyst showed 100% elimination of benzaldehyde in all conditions. Hydrogen addition did not have any beneficial effects on catalytic HC conversion. Abstract: In this study a qualitative and quantitative analysis of carbonyl compound emissions from exhaust gas of homogeneous charge compression ignition (HCCI) and spark ignition (SI) engines, trapped on dinitrophenylhydrazine (DNPH) solution, were investigated. The hydrazine formed were analysed by means of HPLC and detected with ultraviolet (UV) detector. 15 standards of carbonyl – DNPH derivatives were identified and compared with engine emissions before and after catalyst. Emissions compounds such as formaldehyde (HCHO), acetaldehyde (CH3 CHO), and acrolein (H2 CHCHO) are of interest to the scientific and regulatory communities due to their suspected or likely impacts on human health. The frequent exhaust products of the two engine operation modes were, acetaldehyde followed by acrolein, m-tolualdehyde, benzaldehyde (C6 H5 CHO) and formaldehyde; other aldehydes in the exhaust gas were observed to be very small. The percentage contribution of carbonyl compounds to the total hydrocarbon (THC) emissions in this study lies between 2.6–4.5% for HCCI stoichiometric and 5.5–8.4% for HCCI lean operation. These results indicate that engine-operating conditions appear to exert a strong influence on the total mass emissions of carbonyls measured before catalyst. The prototype catalytic converter eliminates most of the carbonyls species in the exhaust in both combustion modes except for acetaldehyde species, a negative conversion presented for all engine conditions. A prototype catalyst showed high efficient conversion on aromatic and unsaturated aldehyde for both engine modes.